On the classes of analytic functions involving A1-Oboudi operator - Mahzoon, Hesam (Tamsui Oxford Journal of Mathematical Sciences)
In this note, we define the new subclasses N m,n(b, α, β, λ) and̃Nm,b, α, β, λ) of analytic functions using the Al -oboudi operator. For functions belonging to these classes we determine coefficient inequalities, extremepoints and integral means inequalities.